Digitalization and the Anthropocene - Creutzig, Felix; Acemoglu, Daron; Bai, Xuemei; Edwards, Paul N.; Hintz, Marie Josefine; Kaack, Lynn H.; Kilkis, Siir; Kunkel, Stefanie; Luers, Amy; Milojevic-Dupont, Nikola; Rejeski, Dave; Renn, Jürgen; et al. (Annual Review of Environment and Resources, 2022)
Great claims have been made about the benefits of dematerialization in a digital service economy. However, digitalization has historically increased environmental impacts at local and planetary scales, affecting labor markets, resource use, governance, and power relationships. Here we study the past, present, and future of digitalization through the lens of three interdependent elements of the Anthropocene: (a) planetary boundaries and stability, (b) equity within and between countries, and (c) human agency and governance, mediated via (i) increasing resource efficiency, (ii) accelerating consumption and scale effects, (iii) expanding political and economic control, and (iv) deteriorating social cohesion. While direct environmental impacts matter, the indirect and systemic effects of digitalization are more profoundly reshaping the relationship between humans, technosphere and planet. We develop three scenarios: planetary instability, green but inhumane, and deliberate for the good. We conclude with identifying leverage points that shift human–digital–Earth interactions toward sustainability.